Task Performance in IT: The Critical Roles of Organisational Citizenship and Innovative Behaviours (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This research is focused on uncovering the effect of Organisational Citizenship Behaviour (OCB) and Innovative Work Behaviour (IWB) on task completion of IT professionals of the National Capital Region (NCR) in India. The research was undertaken using a structured survey of 100 IT professionals which concentrated on dimensions such as altruism, courtesy, conscientiousness, sportsmanship, and civic virtue (OCB) in addition to creativity, ideation and problem-solving agility (IWB). Factual or inferential statistical methods like t-tests, and SpSS find that OBC has a relationship with better teamwork and mutual help although it itself doesn’t have a direct relationship with task performance. However, IWB factors were not significantly correlated with task performance. Research shows that although positive worker conduct generally creates a productive working environment, it may not have a direct influence on productivity and depends on other factors. The current research provides a new perspective on the relationship of OCB and IWB to the performance of IT professionals, this suggests that future studies on organisational behaviour in the IT sector will elaborate more on these aspects.